2012
DOI: 10.1159/000341426
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Refined Tenocyte Differentiation Culture Technique for Tendon Tissue Engineering

Abstract: We have established that human tenocytes can differentiate in the absence of exogenous fetal bovine serum (FBS) but in the presence of insulin-like growth factor-1 (IGF-1) and transforming growth factor-β3 (TGF-β3). The extent of tenocyte differentiation was assessed by examining cell survival, collagen synthesis, cell morphology and expression of tenocyte differentiation markers such as scleraxis (Scx), tenomodulin (Tnmd), collagen type I (Col-I) and decorin (Dcn). Our results indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 93 publications
3
21
0
Order By: Relevance
“…SCX, TNMD, and DCN, has been reported in the presence of IGF-1 and TGF-β 3 in 2D cultures [Qiu et al, 2013]. Interestingly, in our experimental conditions, expression of SCX and TNMD could be regained not only at low passages (e.g.…”
Section: Discussionsupporting
confidence: 58%
“…SCX, TNMD, and DCN, has been reported in the presence of IGF-1 and TGF-β 3 in 2D cultures [Qiu et al, 2013]. Interestingly, in our experimental conditions, expression of SCX and TNMD could be regained not only at low passages (e.g.…”
Section: Discussionsupporting
confidence: 58%
“…Caliari et al [22] demonstrated that IGF-1 at concentrations ranging from 10 to 200 ng/ml was capable of significantly enhancing COL1A2, COL3A1 and decorin (DCN) gene expression in equine tenocytes cultured in collagen scaffolds in the absence of serum for 7 days. By contrast, a study performed by Qiu et al [24] demonstrated that IGF-I (50 ng/ml) alone was unable to significantly influence COL1, SCX or TNMD expression in human tenocytes. However, incubation of cells with TGF-b3 (10 ng/ml), or TGF-b3 and IGF-1 together, significantly enhanced gene expression above that of control cultures incubated in the presence of serumsupplemented growth medium.…”
Section: Discussionmentioning
confidence: 80%
“…This has been highlighted in several studies in which the expression of tendon-associated markers, including COL1, COL3, SCX and TNMD, were shown to be downregulated in tenocytes cultured for extended periods [19,20]. These limitations however, could be overcome to some degree by incorporation of tenocytes into 3D culture systems [25,27,41] or through the addition of specific growth factors [22,24,25]. In the current report, we initially investigated the effectiveness of culturing equine tenocytes as hanging drops as a means by which to generate scaffold-free 3D microtissue spheroids.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, PDGF receptor expression is increased in diseased tendons, and is associated with hypercellularity 32 , and taken into context with our findings on the poor effects of PDGF on tendon-related genes, this suggests that PDGF may not be the most suitable factor for improving tendon healing outcomes. IGF-1 and TGF-β are both present within the tendon matrix 18 , and in vitro have been shown to be involved in tendon cell growth, collagen production and matrix remodelling [19][20][21][22][23][24][25] . Developmental studies suggest a key role for TGFβ1 in tendon development 33 , and inhibiting TGFβ1 has generally resulted in poor healing outcomes in in vivo tendon defect models 34 .…”
Section: Discussionmentioning
confidence: 99%
“…These were chosen as PDGF is among the most widely studied tendon factors, and IGF-1 and TGF-β are both present within the tendon matrix. Furthermore, all are upregulated during tendon healing, and are known to enhance tendon cell growth, collagen production and matrix remodelling, in vitro [18][19][20][21][22][23][24][25][26] . Furthermore, we have focussed on not only classical tendon-related outputs, such as cell proliferation and collagen production, we have also assessed the tenocyte gene expression profile, assessing genes important in tenocyte, chondrocyte and osteoblast biology.…”
Section: Introductionmentioning
confidence: 99%